Kompetencje lubuskiego lidera = Competence of the Lubuskie province leader - Korcz, Iwona (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article is devoted to the competence of the leader of the Lubuskie province in politics and business. The analysis of competence profiles of such leaders, including psychological, praxeological and sociological competence, is preceded by a theoretical introduction to competence.
Keywords: województwo lubuskie; lider; kompetencje